Mapping the Fine Arts Landscape in the Millennial Era as Trends and Challenges - Hulfadila, Hulfadila (Professorline, 2024)
This article maps the trends and challenges faced by the fine arts industry in the millennial era. The increasingly large and influential millennial generation has changed the landscape of contemporary art, driven by developments in digital technology and social media. Trends identified include the increasing accessibility of fine art, collaborative and interdisciplinary art, as well as the central role of millennial audiences in the industry ecosystem. On the other hand, millennial artists face challenges in building sustainable careers, limited funding and institutional support, intellectual property rights issues, and maintaining long-term audience engagement. Understanding the dynamics of these trends and challenges is important for stakeholders to formulate adaptive and innovative strategies to encourage the sustainability and growth of the fine arts industry in the millennial era.